2017
DOI: 10.1021/acs.inorgchem.7b02276
|View full text |Cite
|
Sign up to set email alerts
|

Introducing NacNac-Like Bis(4,6-isopropylbenzoxazol-2-yl)methanide in s-Block Metal Coordination

Abstract: Within this work, the field of bulky methanides in metal coordination is exceeded by the synthesis of the versatile and promising bis(4,6-isopropylbenzoxazol-2-yl)methane (7) ligand platform. As an enhancement in this class of ligands, isopropyl (iPr) substituents as steric-demanding groups have been successfully introduced in proximity to the coordination pocket, mimicking the shielding abilities of the ubiquitous NacNac ligand scaffold to improve the steric protection of a coordinated s-block metal cation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 93 publications
1
26
0
Order By: Relevance
“…[25][26][27] Due to their relevance to porphyrins and the fluorescent properties of BODIPY dyes and related complexes, 28 dipyrrins have been extensively studied and shown to exhibit redox activity in their complexes and dipyrrin-fullerene triads. [29][30][31][32][33][34][35] Similarly to these studies, we have shown that a simply prepared anionic, imine-expanded dipyrrin acts as a ligand for iron and uranium complexes, 36 the latter showing ligand redox activity. 37 Due to the ligand-based LUMO, the sequential outer-sphere, one-electron reduction of the uranyl(VI) center to U(V) and U(IV) occurs by initial ligand reduction followed by electron-transfer to the metal.…”
Section: Introductionmentioning
confidence: 75%
“…[25][26][27] Due to their relevance to porphyrins and the fluorescent properties of BODIPY dyes and related complexes, 28 dipyrrins have been extensively studied and shown to exhibit redox activity in their complexes and dipyrrin-fullerene triads. [29][30][31][32][33][34][35] Similarly to these studies, we have shown that a simply prepared anionic, imine-expanded dipyrrin acts as a ligand for iron and uranium complexes, 36 the latter showing ligand redox activity. 37 Due to the ligand-based LUMO, the sequential outer-sphere, one-electron reduction of the uranyl(VI) center to U(V) and U(IV) occurs by initial ligand reduction followed by electron-transfer to the metal.…”
Section: Introductionmentioning
confidence: 75%
“…To better mimic and finally complement the shielding abilities of the famous NacNac ligand scaffold, steric demanding substituents were introduced at the 4‐position adjacent to the coordination pocket. Starting with methyl groups in bis(4‐Me‐benzoxazol‐2‐yl)methane ( C ), the steric bulk was successively increased by the introduction of isopropyl‐ ( D ) and tert ‐butyl ( E ) residues in the corresponding bis(4,6‐R‐benzoxazol‐2‐yl) (R = i Pr, t Bu) derivatives.…”
Section: Varieties Of Bridged (Benzheterocyclo) Ligand Scaffoldsmentioning
confidence: 99%
“…After preparation of the corresponding 3,5‐substituted 2‐aminophenol derivatives starting from 3,5‐isopropyl‐ or 3,5‐ tert ‐butylphenol, ligand platforms D and E are accessed according to procedure ( c ) depicted in Scheme . As a highlight, treatment of D and E with a magnesium chloride Hauser‐base gives the corresponding D ‐supported magnesium(II) chloride complexes (Scheme ) , …”
Section: Highlights Of Bis(benzoxazol‐2‐yl)methanes C‐e In Main‐groupmentioning
confidence: 99%
See 2 more Smart Citations